Kesiapan Perawat Unit Hemodialisa Dalam Menghadapi Adaptasi Kebiasaan Baru Pandemi Covid-19 - Vivi Retno Intening; Agata Wilis Widya Anggrita; Aknes Matitamole; Debora Yusi Kusumastuti; Delia Delia; Priska Anggelina Febria; Rahajeng Kartika; Silvester Trias Nugroho (Jurnal Penelitian Kesehatan SUARA FORIKES, 2021)
Background: A Healthcare worker has a significant role, as well as plays a frontline in providing health intervention in relation to recent Covid-19 pandemic. He/she is vulnerably exposed to hazards such as psychological pressure, physical and mental exhaustion and the stigma imposed by society. Among other health care duties, a nurse possesses a responsibility as a care giver in which he/she needs to provide helps for patient physically and psychologically while also upholds the client's dignity. Awareness is a state-condition where a person is ready to respond or answer challenges in a certain way to a particular situation. A nurse who has the duty in Hemodialysis Unit, who is in charge of caring for patients with Chronic Renal Failure (CRF) with routine hemodialysis therapy are potentially at risk of being exposed to the Covid-19 virus during this pandemic. For this situation, a nurse needs to have awareness to remain able to carry out hemodialysis to CRF patients. Objectives: This study aims to determine the awareness of a nurse in facing the adaptation of new normal in the Covid-19 pandemic. Methods: This research was a quantitative survey applying in-depth interviews. This research used qualitative phenomenology approach, by analyzing the results of interviews with coding, determining categories, and determining the theme of the interview results. Results: The results of in-depth interviews with 6 hemodialysis unit nurses in a private hospital in the Yogyakarta region, obtained 65 codes, 18 categories, and 5 themes. Conclusion: The awareness of the adaptation of new normal in the Covid-19 pandemic possesses by each nurse in Hemodialysis Unit is vary. However, the nurses aware, that to be able to continuously provide nursing care to CRF patients with routine hemodialysis therapy, they need to be mindful to their physical and psychological self-awareness; to well-prepare any Personal Protective Equipment (PPE) and to conform PPE standards used in HD units. They generate a commitment to remain on duty during a pandemic Covid-19. Keywords: nurse awareness; hemodialysis; Covid-19 pandemic; new normal ABSTRAK Latar belakang: Tenaga kesehatan memiliki peran yang sangat penting dan berperan sebagai garda terdepan dalam memberikan tindakan terhadap wabah Covid-19. Petugas kesehatan dapat terpapar bahaya seperti tekanan psikologis, kelelahan fisik serta mental dan stigma yang diberikan oleh masyarakat. Salah satu tugas perawat yaitu sebagai pemberi perawatan (care giver) yang merupakan tindakan membantu klien secara fisik maupun psikologis sambil memelihara martabat klien. Kesiapan (awareness) merupakan kondisi seseorang yang membuatnya siap untuk memberikan respon atau jawaban dalam cara tertentu terhadap suatu situasi. Perawat yang bertugas di Unit Hemodialisa, yang bertugas merawat pasien dengan Gagal ginjal Kronik (GGK) dengan terapi rutin hemodialysis sangat beresiko terpapar virus Covid-19 pada masa pandemi ini, dan kesiapan perawat sangat diperlukan untuk tetap mampu melaksanakan hemodialisis kepada pasien GGK. Tujuan: Penelitian ini bertujuan mengetahui kesiapan perawat dalam menghadapi adaptasi kebiasaan baru pandemi Covid-19. Metode: Penelitian ini termasuk dalam penelitian survei kualitatif dengan wawancara mendalam. Pendekatan yang dilakukan adalah kualitatif phenomenology, dengan menganalisis hasil wawancara dengan koding, menentukan kategori, dan menentukan tema dari hasil wawancara. Hasil: Hasil wawancara mendalam kepada 6 perawat unit hemodialisis di rumah Sakit swasta di wilayah Yogyakarta, didapatkan 65 kode, 18 kategori, dan 5 tema. Kesimpulan: Kesiapan perawat unit hemodialisa dalam menghadapi adaptasi kebiasaan baru pada masa pandemi Covid-19 sangat beragam. Kesiapan yang dilakukan perawat untuk tetap dapat melakukan asuhan keperawatan pada pasien GGK dengan terapi rutin hemodialisa meliputi kesiapan diri secara fisik dan psikologis, kesiapan Alat Pelindung Diri (APD) dan standar APD yang digunakan di unit HD, sehingga menimbulkan komitmen untuk tetap bertugas dalam masa pandemi Covid-19 menuju era adaptasi kebiasaan baru. Kata kunci: kesiapan perawat: hemodialisa; pandemi Covid-19; adaptasi kebiasaan baru